2004
DOI: 10.1161/01.hyp.0000116224.51189.80
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variant in the α 2B Adrenoceptor Gene, a Positional Candidate on Chromosome 2, Associates With Hypertension

Abstract: Abstract-In a genome-wide scan in Scandinavians, we found suggestive linkage between early-onset primary hypertension and a region on chromosome 2. The ␣ 2B -adrenoceptor gene, a candidate gene within this region, harbors a functional insertion/deletion (I/D) polymorphism of three glutamate residues. The aim of this study was to investigate if the DD genotype is associated with hypertension in Swedes. We performed an association study between the I/D polymorphism of the ␣ 2B -adrenoceptor and hypertension in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
(30 reference statements)
7
33
1
Order By: Relevance
“…With respect to hypertension, our data in the large cohorts are consistent with an earlier study with a smaller sample 20 but contrast with those of Von Wowern et al (2004), 21 who showed an increased risk (ORϭ2.01) for early-onset (younger than 50 years old) hypertension in Swedish ␣ 2B -AR Del/Del homozygotes, an effect that lost significance in an all-age population. Even when we stratified our data and compared younger versus older subjects (using age 40, as reported, or when we used age 50 as a cutoff, data not shown), we failed to find evidence to support the conclusions of Von Wowern et al (2004), perhaps because of differences between our white population and their more ethnically homogenous Swedish population.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…With respect to hypertension, our data in the large cohorts are consistent with an earlier study with a smaller sample 20 but contrast with those of Von Wowern et al (2004), 21 who showed an increased risk (ORϭ2.01) for early-onset (younger than 50 years old) hypertension in Swedish ␣ 2B -AR Del/Del homozygotes, an effect that lost significance in an all-age population. Even when we stratified our data and compared younger versus older subjects (using age 40, as reported, or when we used age 50 as a cutoff, data not shown), we failed to find evidence to support the conclusions of Von Wowern et al (2004), perhaps because of differences between our white population and their more ethnically homogenous Swedish population.…”
Section: Discussionsupporting
confidence: 82%
“…We did not observe statistically significant association with the SNPs at ␣ 2A -AR and ␣ 2C -AR; however, we observed a trend for association with the ␣ 2B -AR SNP. This result, coupled with evidence for association of a variant in that receptor with early-onset hypertension, 21 led us to undertake more thorough sequencing and genotyping studies on ␣ 2B -AR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] With the accumulated evidence for the implication of 2q23 to q36 in harboring loci, which may influence control of bp, the focus is now on taking such studies forward into candidate gene analysis. 28 Haplotype analysis of our Kyrgyz pedigree has suggested a small interval that may be responsible for the premature hypertensive phenotype. The current release of the human genome assembly, available through Ensembl (www.ensembl.org), indicates that the 2q24.3 to q31.1 region between markers D2S2380 and D2S335 (166.5 to 175.9 cM) spans Ͻ9 megabase pairs and encompasses 36 genes of known or predicted function.…”
Section: Discussionmentioning
confidence: 89%
“…The human  2B -adrenoceptor is encoded by the ADRA2B gene located on chromosome 2q12 (Regan et al 1988). A common variant form of the this gene which encodes a receptor protein with a insertion/deletion (I/D) of three glutamate residues located in the third intracellular loop of the receptor has been associated with EHT (Lockette et al1995;Wowern et al 2004). …”
Section: Sympathetic Nervous Systemmentioning
confidence: 99%